Price co-integration analyses of food crop markets: The case of wheat and teff commodities in Northern Ethiopia - Jaleta, Moti; Gebremedhin, Berhanu (Academic Journals, 2012)
This paper examines the role of market price information dissemination on the co-integration of grain market prices in Northern Ethiopia. Results are based on bi-monthly retail price data on wheat and teff commodities collected from six markets in the Tigray region of Northern Ethiopia. The data has 55 observations for each of the two crops in each of the six markets ranging over a period from May, 2006 to October, 2008. Johansen’s co-integration test reveals that most markets are co-integrated in wheat and teff retail prices. However, there is an indication that retail prices at Abi-Adi, a town located relatively farther away from the main asphalt road is less integrated to other markets. This implies that, in addition to market price information dissemination, other infrastructural developments like road networks are crucial for spatial market integration through the physical transfer of goods from one market to another.